The impact of management accounting and how it can be implemented into the organizational culture - Ahmed Mohamed Ameen; Moataz Fathi Ahmed; Meral Ahmed Abd Hafez (Dutch Journal of Finance and Management, 2018)
Management accounting is increasingly becoming a critical decision making process in organizations across the world. Value in any organization has to do with the ability to generate profits and solve societal issues within the environment which the organization exists. This publication not only encourages the utilization of this system but also promotes the consistent application through the recommended approaches as discussed. To ensure consistency once the process of management accounting is adopted, it has to be adopted as a culture within the organization. This form of accounting, just like financial accounting is a type of enterprise management financial management tool, however, in MA, operations are analyzed for strategic decision making but in FA operations and costs ae analyzed mainly for reporting convincing investors on the sustainability of the business.
Keywords: 650; management; culture; organizational; management accounting; accounting business